The National Cowboy and Western Heritage Museum : changing visions of the West - Weaver, Bobby D. (Bobby Dearl), 1936- (Nancy and Ted Paup '74 ranching heritage series., 2020)
In June 1965, the National Cowboy Hall of Fame and Western Heritage Center, as it was then named, owned a mere handful of artifacts. In fact, the Oklahoma City institution was forced to borrow materials in order to mount exhibitions to support its inaugural events. From that modest beginning, the center, now known as the National Cowboy and Western Heritage Museum, has grown into perhaps the world?s most respected repository for the study and understanding of the diverse cultures of the American West.But, as Bobby D. Weaver demonstrates in this no-holds-barred history, the path from those humble origins to the esteemed position the museum occupies today led through some rough-and-tumble times, including a period of receivership. The autocratic style of the founding director, coupled with certain early less-than-ethical practices, forced the museum into what Weaver delicately terms "a legal tangle" that required a complete organizational and financial overhaul.With renewed professional leadership and the steadfast support of dedicated patrons and sponsors, the National Cowboy and Western Heritage Museum has developed and changed along with evolving understandings of the culture it was founded to celebrate. What was once a shrine to a particular manifestation of American frontier life has transformed into a world-class art and historical museum that represents the broad sweep of the American West?both lived and imagined?with its full range of social, ethnic, and economic diversity. As Weaver relates, today?s institution is well poised for the future as it furthers its mission of preserving and interpreting the heritage of a vital American region and its lifeways.